PHYSIOLOGICAL PARAMETERS OF ARTIFICIAL BLOOD CIRCULATION FROM THE POSITION OF THE EVIDENCE BASED MEDICINE. PART I - I. A. Kornilov; D. N. Ponomarev; V. A. Shmyrev; A. A. Skopets; Yu. S. Sinelnikov; V. V. Lomivorotov (Вестник анестезиологии и реаниматологии)
Abstract. Artificial blood circulation is a main supporting technique of cardiac surgery. This review is devoted to the management aspects of main physiological parameters during artificial blood circulation in the adult patients from the position of the evidence based medicine.